INEQUALITY OF ACCESS TO PSYCHOSOCIAL SERVICES AND PHYSICAL ACTIVITY-BASED SOLUTIONS: A CASE STUDY OF STUDENTS IN SOUTH PAPUA - Riyanto, Pulung; Rosman, Deden Budi (Journal of Physical Education, Health and Sports Recreation, 2025)
This study aims to examine the role of physical activity as an alternative solution to limited access to psychosocial services for students in South Papua, specifically at Musamus University, Merauke. Using a descriptive qualitative approach with a case study method, data were collected through in-depth interviews, participant observation, and documentation from eight purposively selected Physical Education students. The results indicate that students face serious limitations in accessing psychosocial services, exacerbated by the lack of professional staff and cultural stigma. Physical activity is an effective non-clinical coping mechanism, offering emotional and social benefits while strengthening emotional regulation. It also creates an inclusive social environment and fosters cohesion among students from diverse cultural backgrounds. These findings underscore the need to develop a healthy campus strategy based on physical activity as an adaptive approach to improving the emotional well-being of students in underdeveloped regions such as South Papua.